Oxidation of Cinacalcet Hydrochloride by Chloramine-B in Acid Medium: A Kinetic and Mechanistic Study - Kallesha, Nichhapurada; Prasad, Ningegowda; Shivakumara, N.; H. Narasimhamurthy, Kereyagalahally (Asian Journal of Chemistry, 2021)
Kinetic and mechanistic study of cinacalcet hydrochloride by chloramine-B (CAB) in HCl medium at 308 K was the aim of this work. Analyzed the reaction at five different temperatures and determined the thermodynamic parameters using Arrhenius plots. The reaction had a stoichiometry of 1:2 and characterized the oxidation product using chromatographic and spectroscopic methods. The rate law is deduced from the marked effects, which were accompanied by plausible mechanisms.